G3. Intraoperative haemodynamic monitoring during high-risk caesarean section: a comparison between bioreactance (NICOM R) and pressure waveform analysis (LidCOrapidR): preliminary results. (12th August 2016) - Vinayagam, D.; Bampoe, S.; Thilaganathan, B.; Khalil, A.
Abstract: Background : Intraoperative haemodynamic monitoring is carried out in high-risk surgical patients, often using invasive methods, including pulmonary artery catheterisation. Early goal-directed therapy in high-risk surgical patients reduces tissue hypoxia, organ failure and improves outcomes. Significant maternal morbidity arises as a result of perioperative haemorrhage. At present, heart rate and brachial blood pressure are used as proxy markers to aid in fluid resuscitation, however, we know that these exhibit minimal change during early stages of shock, and are poor indicators of the adequacy of therapeutic intervention. Objective : The aim of this study was to compare the cardiac output trends observed during C-section for morbidly adherent placenta, using NICOM® and LiDCOrapid®. Methods : This is an ongoing, prospective observational study in women undergoing planned high-risk surgery for morbidly adherent placenta in a tertiary centre. Cardiac output estimations were collected at 2 min intervals, over 60 min. A total of 155 paired datasets were collected. Results : We present a case series of temporal intraoperative cardiac output trends using NICOM® and LiDCOrapid®, along with the percentage changes observed when compared to the pre-operative baseline and correlation analysis. Conclusions : NICOM® appears to be a promising, non-invasive device to display real-time intraoperative haemodynamic trends during postpartum haemorrhage.